2018
DOI: 10.15288/jsad.2018.79.229
|View full text |Cite
|
Sign up to set email alerts
|

The Translational Value of Psychophysiology Methods and Mechanisms: Multilevel, Dynamic, Personalized

Abstract: It has been nearly 15 years since Kazdin and Nock published methodological and research recommendations for understanding mechanisms of change in child and adolescent therapy. Their arguments and enthusiasm for research on mechanisms of behavior change (MOBCs) resonated across disciplines and disorders, as it shined a light on the crucial importance of understanding how and for whom treatments instigate behavior change and how therapeutic mechanisms might be extended to "situations and settings of everyday lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 81 publications
(95 reference statements)
0
16
0
Order By: Relevance
“…In line with well‐established evidence that people often drink alcohol to modify emotional states and decrease inhibition (e.g., Cooper et al, ; Labouvie and Bates, ; Patrick and Schulenberg, ), LS to alcohol effects on cardiovascular regulation could promote risk by increasing the amount of alcohol needed to achieve desired effects of drinking, such as increased sociability and disinhibition and decreased negative affect (Schuckit, ; Schuckit, ; Schuckit et al, ). From an integrated brain–body perspective (Buckman et al, ), the decreases in HRV that have been observed in multiple laboratories following oral alcohol ingestion (reviewed in Ralevski et al, ) would serve to alter communication between the cardiovascular system and the brain areas involved in cardiovascular regulation (Benarroch, ; Goldstein, ). These brain areas, collectively referred to as the central autonomic network, include neural relay and integration areas extending from nuclei in the brainstem, through midbrain to extended limbic and prefrontal regions that participate in cognitive, emotional, and behavioral control.…”
Section: Discussionmentioning
confidence: 99%
“…In line with well‐established evidence that people often drink alcohol to modify emotional states and decrease inhibition (e.g., Cooper et al, ; Labouvie and Bates, ; Patrick and Schulenberg, ), LS to alcohol effects on cardiovascular regulation could promote risk by increasing the amount of alcohol needed to achieve desired effects of drinking, such as increased sociability and disinhibition and decreased negative affect (Schuckit, ; Schuckit, ; Schuckit et al, ). From an integrated brain–body perspective (Buckman et al, ), the decreases in HRV that have been observed in multiple laboratories following oral alcohol ingestion (reviewed in Ralevski et al, ) would serve to alter communication between the cardiovascular system and the brain areas involved in cardiovascular regulation (Benarroch, ; Goldstein, ). These brain areas, collectively referred to as the central autonomic network, include neural relay and integration areas extending from nuclei in the brainstem, through midbrain to extended limbic and prefrontal regions that participate in cognitive, emotional, and behavioral control.…”
Section: Discussionmentioning
confidence: 99%
“…The initial stage of determining the level of psychophysiological readiness of students to successfully mastering the learning material and mastering practical skills is considered to be a comprehensive assessment of the peculiarities of the development of indicators of the functional state of higher nervous activity. First of all, it concerns its high-speed characteristics, above all simple visual-motor reaction, the indicators of which provide an opportunity to fully adequately determine the degree of formation of indicators of visual-motor coordination capabilities, which are at the basis of ensuring the adequate implementation of various socio-and professionally significant sensory-motor acts and, consequently, motor skills necessary for successful theoretical and practical activities in institutions of higher education of future medical professionals [2,5,8,12,17,20,25,29,32].…”
Section: Discussionmentioning
confidence: 99%
“…Another important indicator of the complex assessment of the peculiarities of the development of indicators of the functional state of higher nervous activity should be considered determination of the degree of formation of criterion characteristics of audio-motor or auditory-motor coordination capabilities and, respectively, indicators of the latent period of audio-motor reaction, which are also at the basis of effective implementation of various socially-and professionally significant sensory-motor acts and, consequently, the various motor techniques necessary for a successful theorist and the practical activities of medical students [2,7,8,10,17,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key problems of modern biomedical anthropology is the scientific substantiation of the prerequisites for the formation of a healthy lifestyle, enhancement of adaptive resources of its organism and quality of life, introduction into the process of vital functions of health-saving technologies that take into account the morphological, psychophysiological and personality features of the person and based on the results of the medical-ecological monitoring of the modern population [1,4,8,18,32,34,35].…”
Section: Introductionmentioning
confidence: 99%